THE IMPACT OF ECOLOGICAL REHABILITATION PROGRAMS ON KIDNEY FUNCTION AND OVERALL HEALTH IN PATIENTS WITH CHRONIC GLOMERULONEPHRITIS - Sapayeva Z.A; Jumaniyazov B.K; Zaripov Z.O (Scholar Express Journals, 2025)
This research aims to evaluate the effectiveness of ecological rehabilitation programs in improving the health of individuals suffering from chronic glomerulonephritis (CGN). The study included 100 participants, with 50 of them undergoing an ecological rehabilitation program. The program provided interventions aimed at enhancing air and water quality, improving living conditions, and reducing stress. Results indicated that the ecological rehabilitation led to noticeable improvements in kidney function and the overall health of the participants.
Keywords: chronic glomerulonephritis; ecological rehabilitation; kidney function